THE DEVELOPMENT OF FORMAL ENVIRONMENTAL EDUCATION AS A INTERDISCIPLINARY OBJECT AND ITS PRACTICE IN EVERYDAY SCHOOL (CIPEEX, 2022)
THIS ARTICLE IS A SMALL DISCUSSION ABOUT THE PRESENCE OF ENVIRONMENTAL EDUCATION (EE) IN COLGIO ESTADUAL DE TEMPO INTEGRAL SANTA TEREZINHA, LOCATED IN THE MUNICIPALITY OF ITAPACI-GO. THE SCHOOL OFFERS INTEGRAL EDUCATION TO 346 STUDENTS AND IN ITS FACULTY; IT HAS 36 PROFESSORS GRADUATED IN ALL AREAS OF KNOWLEDGE. IN THE APPLICATION OF EE IN THE SCHOOL ROUTINE, IT IS WORTH EMPHASIZING FACTORS SUCH AS THE IMPORTANCE OF THE ENVIRONMENT FOR THE MAINTENANCE OF LIFE ON PLANET EARTH, THE CURRENT ENVIRONMENTAL PROBLEM AND POSSIBLE IMMEDIATE AND LASTING SOLUTIONS TO SUCH PROBLEMS. IT IS IMPORTANT TO CLASSIFY AND DIFFERENTIATE FORMAL AND NON-FORMAL ENVIRONMENTAL EDUCATION, SO THAT PEDAGOGICAL PRACTICE MEETS LEARNING IN AN INTEGRAL AND EFFICIENT WAY. THE DEFINITION OF ENVIRONMENTAL EDUCATION AND THE LEGISLATION THAT REGULATES ACTIVITIES RELATED TO THE THEME ARE PART OF ITS APPLICATION IN THE SCHOOL ROUTINE, WHICH FOLLOWS A CURRICULUM PROPOSED BY THE STATE GOVERNMENT. SOMETIMES THE SCHOOL UNIT AND THE TEACHERS FACE PROBLEMS IN THE APPLICATION OF EE IN THE SCHOOL ROUTINE, HOWEVER, IT SEEKS STRATEGIES AND METHODS IN ORDER TO EXECUTE AND DEVELOP IT DAILY AND CONTINUOUSLY. IN THIS WAY, THE RESEARCH WAS BASED ON A BIBLIOGRAPHIC SURVEY WITH A QUALITATIVE APPROACH, IN THE SEARCH TO ANSWER THE KEY PROBLEM OF THE RESEARCH: IS FORMAL ENVIRONMENTAL EDUCATION PRESENT IN THE PEDAGOGICAL ROUTINE OF CEPI SANTA TEREZINHA?
Keywords: educação ambiental; legislação ambiental; meio ambiente